2021
DOI: 10.1038/s41598-021-92717-8
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of COVID-19 recovered patients with mild disease

Abstract: COVID-19 may manifest as mild, moderate or severe disease with each grade of severity having its own features and post-viral implications. With the rising burden of the pandemic, it is vital to identify not only active disease but any post-recovery complications as well. This study was conducted with the aim of identifying the presence of post-viral symptomatology in patients recovered from mild COVID-19 disease. Presence or absence of 11 post-viral symptoms was recorded and we found that 8 of the 11 studied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 16 publications
2
27
0
4
Order By: Relevance
“…Increased frequency of post-acute symptoms in females compared to males and slower recovery in females have also been reported in other studies 1113,15,16 , whereas the evidence regarding the influence of age is somewhat contradicting. In one study, an inverted-U formed association between age and worsening of health after infection was observed, similar to the present study, where the majority of symptoms were most frequently reported by the middle-aged (30-59 years) 14 , but reports of increased risk in older individuals 12,28 , young adults 17 , or no effect 11 also exist.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Increased frequency of post-acute symptoms in females compared to males and slower recovery in females have also been reported in other studies 1113,15,16 , whereas the evidence regarding the influence of age is somewhat contradicting. In one study, an inverted-U formed association between age and worsening of health after infection was observed, similar to the present study, where the majority of symptoms were most frequently reported by the middle-aged (30-59 years) 14 , but reports of increased risk in older individuals 12,28 , young adults 17 , or no effect 11 also exist.…”
Section: Discussionsupporting
confidence: 57%
“…Parametric g-computation 10 on logistic regression was used to estimate RDs (with 95% confidence intervals) among the exposed with adjustment for completion time (6, 9 or 12 months), age, sex, obesity, comorbidities from the questionnaire, Charlson Comorbidity Index scores and healthcare occupation. Based on results of other studies [11][12][13][14][15][16][17] , these variables were considered potential confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited on the basis of informed consent and ethical approval was taken from the institution reviewer committee of The University of Lahore, Pakistan. The Sample size was seventy as calculated by epitool [ 12 ]. The Convenient sampling technique was applied.…”
Section: Methodsmentioning
confidence: 99%
“…In roughly 20% of patients, these symptoms persist for 3-6 months or longer after they have been cured of COVID-19. Long COVID can also be found in patients with mild COVID-19 [314]. As a result, following severe COVID-19 [311], long COVID requires special attention.…”
Section: Possible Causes Of the Autoimmune And Anti-inflammatory Proc...mentioning
confidence: 99%